2005
DOI: 10.1136/jcp.2005.026492
|View full text |Cite
|
Sign up to set email alerts
|

Evidence based criteria for the histopathological diagnosis of toxoplasmic lymphadenopathy

Abstract: Aims: To formulate evidence based histopathological criteria for the diagnosis of acquired toxoplasmic lymphadenitis, in an area of high tuberculosis prevalence. Methods: Multiple histopathological parameters were assessed in a consecutive sample of biopsies from 68 patients presenting with lymphadenopathy with a duration of less than six months. Serum IgM enzyme linked immunosorbent assay was used as the standard reference test for the diagnosis of toxoplasmic lymphadenitis. The sensitivity, specificity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 12 publications
2
11
0
3
Order By: Relevance
“…10,11 In this study group, positive antibody carriage of only 35.3 % was observed among patients histologically diagnosed as having Toxoplasma lymphadenopathy, indicating low reliability of histology in the diagnosis of toxoplasmic lymphadenopathy. Findings are comparable to a study done by Eapen et al, 12 while some other studies have reported even lower figures of 22.5 %. 13 Diagnosis of toxoplasmosis can be done by a number of methods, either directly by PCR, hybridization, histology and isolation or via serological methods.…”
Section: Discussionsupporting
confidence: 79%
“…10,11 In this study group, positive antibody carriage of only 35.3 % was observed among patients histologically diagnosed as having Toxoplasma lymphadenopathy, indicating low reliability of histology in the diagnosis of toxoplasmic lymphadenopathy. Findings are comparable to a study done by Eapen et al, 12 while some other studies have reported even lower figures of 22.5 %. 13 Diagnosis of toxoplasmosis can be done by a number of methods, either directly by PCR, hybridization, histology and isolation or via serological methods.…”
Section: Discussionsupporting
confidence: 79%
“…The biopsy demonstrated small microgranulomata without associated necrosis closely associated with lymphoid follicles, findings which are consistent with evidence-based criteria for the histological diagnosis of toxoplasmosis 4. The histological examination was verified by three experienced histopathologists and the patient initially responded to treatment targeted at toxoplasmosis.…”
Section: Discussionsupporting
confidence: 76%
“…The presence of these histological abnormalities alone, when typical, can suffice for the diagnosis. However, to increase the diagnostic yield, serological testing is recommended both in patients with the classical histological features and in those patients with atypical histological findings (6,8). It is noteworthy that fine needle aspiration is rarely useful for the diagnosis, since it allows visualization of only a few isolated cells and does not permit the evaluation of lymph node architecture necessary to detect the classical histological features observed for TL (6,8).…”
mentioning
confidence: 99%